Aggresome formation and segregation of inclusions influence toxicity of α-synuclein and synphilin-1 in yeast. (21st September 2011) - Swinnen, Erwin; Büttner, Sabrina; Outeiro, Tiago F.; Galas, Marie-Christine; Madeo, Frank; Winderickx, Joris; Franssens, Vanessa
Abstract : PD (Parkinson's disease) is a neurodegenerative disorder, caused by a selective loss of dopaminergic neurons in the substantia nigra, which affects an increasing number of the elderly population worldwide. One of the major hallmarks of PD is the occurrence of intracellular protein deposits in the dying neurons, termed Lewy bodies, which contain different proteins, including aggregated α-synuclein and its interacting protein synphilin-1. During the last decade, a number of groups developed yeast models that reproduced important features of PD and allowed the deciphering of pathways underlying the cytotoxicity triggered by α-synuclein. Here, we review the recent contributions obtained with yeast models designed to study the presumed pathobiology of synphilin-1. These models pointed towards a crucial role of the sirtuin Sir2 and the chaperonin complex TRiC (TCP-1 ring complex)/CCT (chaperonin containing TCP-1) in handling misfolded and aggregated proteins.